Illusion, Deception and Dehumanization: Neocolonial Reinforcement of Colonial Legacy and the Role of English - Alam, Mohammed Sarwar (IIUC Studies, 2012)
Under the holy mask of civilizing the world, colonizers have done the unholy task of forming and deforming societies to serve their vested interests. Over centuries, they have skillfully dominated colonized societies through illusion, deception and dehumanization. In the face of national liberation movements, they had to retreat physically, but the inhuman legacy they left behind continues to benefit them in the absence of strong resistive decolonizing discourses. Predatory globalization, through destructive development culture is now the prevailing mode of recolonization which is turning our dreams for a just global society into an ever illusive one. In this context, echoing the views expressed in On the Abolition of the English Department (Ngugi: 1968), this paper argues that English Language and Literature departments have been largely responsible for not forming a strong decolonizing culture and discourse. Also, this paper arrives at an understanding that like Caliban in Shakespeare, English Language now, with growing awareness across the globe, could be used to expose, curse and resist deceptions of the recolonizing forces. DOI: http://dx.doi.org/10.3329/iiucs.v7i0.12259 IIUC Studies Vol.7 2011: 55-62